MODERASI BERAGAMA DALAM KELUARGA HINDU UNTUK PEMBENTUKAN SIKAP TOLERANSI KEPADA ANAK USIA DINI: Religious Moderation - Ida Ayu Putu Melly Puspita Dewi; Komang Sri Utari Dewi; I Nyoman Kiriana (Jurnal Pendidikan Agama, 2022)
ABSTRACT Religious Moderation has been discussed by the government through the Minister of Religious Affairs. Religious Moderation is done because lately there are many troubling things related to certain religions. So that Religious Moderation is very much needed for the Unity of the Republic of Indonesia. With those reasons, this article was written because there is a phenomenon in terms of children's character education in increasing tolerance. Religious Tolerance in Indonesia is needed to educate children to be more compassionate and have an attitude that respects each other both in the family environment and in the Indonesian community. There are several families in Indonesia who have different beliefs, and they can live in harmony without disputes. This intrigued the author to write this article, in the author's circle there is 1 family that can live harmoniously and harmoniously despite adhering to different beliefs, namely Hinduism and Islam. Children who grow and develop in the family seem very harmonious and can always appreciate others. This proves , the need for the character of Tolerance in the form to be able respect and love each other between people.